KIAA0556 is a novel ciliary basal body component mutated in Joubert syndrome - Sanders, Anna A. W. M.; de Vrieze, Erik; Alazami, Anas M.; Alzahrani, Fatema; Malarkey, Erik B.; Sorusch, Nasrin; Tebbe, Lars; Kuhns, Stefanie; van Dam, Teunis J. P.; Alhashem, Amal; Tabarki, Brahim; Lu, Qianhao; et al. (Genome biology, 2015)
Joubert syndrome (JBTS) and related disorders are defined by cerebellar malformation (molar tooth sign), together with neurological symptoms of variable expressivity. The ciliary basis of Joubert syndrome related disorders frequently extends the phenotype to tissues such as the eye, kidney, skeleton and craniofacial structures.